Cyclodextrin-based nano-carrier for intelligent delivery of dopamine in a self-healable anti-corrosion coating. Issue 4 (August 2021) - Dehghani, Ali; Bahlakeh, Ghasem; Ramezanzadeh, Bahram; Mofidabadi, Amir Hossein Jafari
Abstract: In the present work, the dopamine (DOP) performance was improved by encapsulation into a novel amphiphilic beta-cyclodextrin ( β -CD) nano-carrier. The inclusion complexes ( β -CD-DOP) structure was identified by Ultraviolet-visible spectroscopy (UV-Vis), Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction analysis (XRD), Raman, and thermal gravimetric analysis (TGA) techniques. TGA assessments confirmed about 33% of DOP encapsulation in the β -CD cavity. The Electrochemical impedance spectroscopy (EIS) measurements in the solution (NaCl) phase after introducing β -CD-DOP have demonstrated 85% of corrosion attack retardation after 5 h iron exposure to 3.5% NaCl electrolyte. The samples were then analyzed via different morphological/elemental approaches, i.e., Field-Emission Scanning Electron Microscopy (FE-SEM), contact angle, Grazing incidence X-Ray diffraction (GIXRD), and Energy-dispersive X-ray spectroscopy (EDS)/Mapping. The self-healing mechanism after introducing β -CD-DOP into the SiC was investigated by EIS. Results confirmed the film resistance enhancement from 5540 Ω.cm 2 to 10, 900 Ω.cm 2 after 1 h steel exposure, affirming a considerable self-healing degree after β -CD-DOP inclusion. The silane-based coating (SiC) defected zone morphology was studied by EDS/Mapping and FE-SEM techniques. Besides, notable resistance enhancement of the intact SiC has (from 13, 032 Ω.cm 2 to 16, 231 Ω.cm 2 ) demonstrated that most of the coating diffusion pathways were blocked by inclusion complexes, which could reduce the electrolyte/ion diffusion. Through Dispersion-corrected density functional theory (DFT-D) based explorations, the inclusion capacity of DOP inside the β -CD was investigated. The adsorption of DOP and β -CD/DOP on the steel substrate was proved by MC/MD calculations. Graphical Abstract: ga1 Highlights: Cyclodextrin-based nano-carrier was selected for dopamine bio-molecule. Self-healable silane coating was designed using beta cyclodextrin-dopamine complexes. The solution phase electrochemical measurements demonstrated the corrosion index was mitigated 85%. The computer calculations displayed the adsorption of beta cyclodextrin-dopamine complexes on the steel substrate.